2008
DOI: 10.1002/path.2295
|View full text |Cite
|
Sign up to set email alerts
|

BRAF provides proliferation and survival signals in MSI colorectal carcinoma cells displaying BRAFV600E but not KRAS mutations

Abstract: BRAF kinase is a downstream target of KRAS and activates the MAPK pathway. These two molecules are prone to mutations in sporadic microsatellite unstable (MSI) colorectal carcinomas (CRC) and BRAF V600E mutations are inversely associated with oncogenic KRAS mutations. The biological significance of BRAF V600E oncogenic activation is not well established in this type of tumour. We aimed to study proliferation and survival effects induced by BRAF inhibition in MSI CRC cell lines harbouring distinct genetic backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 29 publications
2
27
1
1
Order By: Relevance
“…This frequency increases to 70% in colorectal cancers with a microsatellite instability (MSI) phenotype due to hypermethylation of the MLH1 promoter [41][42][43]. In MSI colorectal carcinoma, BRAF mutations occur independently of KRAS mutations and provide proliferation and survival signals through activation of several signaling pathways [44,45]. Cell lines with RAS/BRAF mutations are highly resistant to cetuximab in vitro compared with wild-type cells [46].…”
Section: Biomarkers In Colorectal Cancermentioning
confidence: 99%
“…This frequency increases to 70% in colorectal cancers with a microsatellite instability (MSI) phenotype due to hypermethylation of the MLH1 promoter [41][42][43]. In MSI colorectal carcinoma, BRAF mutations occur independently of KRAS mutations and provide proliferation and survival signals through activation of several signaling pathways [44,45]. Cell lines with RAS/BRAF mutations are highly resistant to cetuximab in vitro compared with wild-type cells [46].…”
Section: Biomarkers In Colorectal Cancermentioning
confidence: 99%
“…BRAF inhibition by small interfering RNA resulted in significantly decreased proliferation and increased apoptosis in the BRAF mutant lines. In contrast, this effect was not seen in the KRAS mutant lines (Preto et al, 2008). Cells carrying BRAF mutations have also been shown to be more sensitive to IOSE29 OSE10 OSE7 SKOV3 OVCAR3 A2780 OVK18 KF28 MDAH2774 OMC3 JHOC5 ES2 MPSC1 POC1 POC2 POC3 WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT WT T1796A T1796A WT WT G35T WT WT G35T MEK inhibitors than cells with RAS mutations (Solit et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…BRAF controls proliferation of human melanoma cells through the regulation of cyclin D1 and cyclindependent kinase inhibitor p27 Kip1 protein (Bhatt et al, 2005(Bhatt et al, , 2007. Similarly, it has been reported that in CRC cells the decreased expression levels of pERK protein and cyclin D1 were more pronounced in cells carrying the BRAF V600E mutation, and, that BRAF V600E -ERK signalling is also important in the regulation of proliferation by p27 Kip1 and cyclin D1 proteins in these cells (Preto et al, 2008).…”
mentioning
confidence: 78%
“…The effect of BRAF knockdown in cellular survival and proliferation is not fully understood. It has been shown that in MSI CRC cell lines, BRAF is the main activator of ERKs and these cells are more dependant on the BRAF -ERK pathway (Preto et al, 2008). Similar to the melanoma model (Bhatt et al, 2005(Bhatt et al, , 2007, in MSI CRC cells, it was shown that BRAF V600E -ERK signalling is important in the regulation of proliferation through the p27 Kip1 and cyclin D1 proteins (Preto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation